Antibody neutralization of HIV-1 and the potential for vaccine design. - Sattentau, Q; Moulard, M; Brivet, B; Botto, F; Guillemot, J; Mondor, I; Poignard, P; Ugolini, S (1999)
Neutralisation by antibody is, for a number of viruses, an in vitro correlate for protection in vivo. For HIV-1 this is controversial. However, the induction of a potent anti-HIV neutralising antibody response remains one of the principal goals in vaccine development. A greater knowledge of the fundamental mechanisms underlying the neutralisation process would help direct research towards suitable vaccine immunogens. The primary determinant of HIV neutralisation appears to be antibody affinity for the trimeric envelope glycoprotein spike on the virion, suggesting that epitope-specific effects are secondary and implying a single, dominant mechanism of neutralisation. Antibody interference with virion attachment to the target cell appears to be a major mechanism of neutralisation by gp120-specific antibodies. This is probably achieved both by antibody-induced dissociation of gp120 from gp41 and by direct inhibition of virus binding to receptor-coreceptor complexes. A gp41-specific antibody neutralises by interfering with post-attachment steps leading to virus membrane fusion. Recent advances in structural analyses of the HIV envelope glycoproteins coupled with data obtained from antibody mapping and neutralisation studies allow a greater understanding of Env function and its inhibition. This in turn should lead to a more rational basis for vaccine design aimed at stimulating highly effective neutralising antibodies.